The Bristol and Bath Railway Path: An Ecopoetic Sound Collaboration. Issue 1 (2nd January 2017) - Prior, Jonathan; Walton, Samantha
Abstract : An ecopoetic sound piece produced in response to the Bristol and Bath Railway Path, UK.